Teaching Strategies for Children with Expressive Language Disorder - Yuniari, Ni Made; Sudarmawan, I Putu Yudi (Universitas Pendidikan Ganesha, 2022)
Students who have communication disorders will need special help from teachers in the regular education environments. This research aims to investigate the English teaching strategies and activities for students with language impairment, especially expressive language disorder. This research used descriptive qualitative research design which focus on literature study from relevance references. The collected data were analysed descriptively, thus the English teaching strategies and classroom management for students with expressive language disorder could be formulated. The result of the study showed that teaching strategies that could improve expressive language are Modelling, Expansion, Choices, Waiting or Withholding, Imitation, Parallel Talk, Picture Communication, Paraphrase, and Place Things Out of the Child’s Reach. Meanwhile, the activities that is suitable to be applied for students with expressive language disorder during instruction through which those activities are also applicable at home practice; wordless books, books with simple text, bubbles, play dough, toy animals, trains sets or car, and play food. Therefore, by implementing those strategies and activities, it is expected the students with expressive language disorder could improve their language competency either in receptive or productive use.